ERRα mediates metabolic adaptations driving lapatinib resistance in breast cancer - Geneviève Deblois (Nature Portfolio, 2016)
Despite initial benefits in treating HER2-positive breast cancer patients with lapatinib, resistance is prevalent. Here the authors show that lapatinib resistance can be ascribed to mTOR-mediated re-activation of ERRα and to the consequent induction of a metabolic adaptation.